Faktor-faktor yang Berhubungan dengan Kekambuhan pada Pasien Malaria di Wilayah Kerja Puskesmas Harapan Kabupaten Jayapura - Awaluddin Awaluddin; Apriliani Yulianti Wuriningsih; Sri Wahyuni (Jurnal Siti Rufaidah, 2025)
Malaria is a global health problem, particularly in tropical countries like Indonesia. Papua has 374 endemic districts/cities, with the highest number of malaria cases, with 14,586 cases, and Jayapura Regency in 2024 with 50,529 patients and 6,213 relapses. The high number of cases is due to the geographical conditions that favor mosquito breeding and the dormant state in the body. If treatment is not carried out correctly and thoroughly, it can lead to malaria relapse. The purpose of this study was to determine factors associated with relapse in malaria patients in the Harapan Community Health Center (Puskesmas) area, Jayapura Regency. This research was an analytical study with a cross-sectional design. Data collection was conducted using a questionnaire. A total of 88 respondents were recruited using simple accidental sampling. The data obtained were statistically analyzed using chi-square and binary logistic regression. Based on the analysis, it was found that factors that were not related to recurrence in malaria patients in the Harapan Community Health Center, Jayapura Regency were age (p-value 1.000 > α 0.05), gender (p-value 0.855 > α 0.05), and education (p-value 0.124 > α 0.05). Factors related to recurrence in malaria patients in the Harapan Community Health Center, Jayapura Regency were occupation (p-value 0.032 or p < α 0.05), nutritional status (p-value 0.000 < α 0.05), and medication adherence (p-value 0.000 < α 0.05). Medication adherence was the dominant factor in recurrence in malaria patients at the Harapan Community Health Center (p-value 0.000 < 0.05). Malaria patients who do not comply with taking their medication cause the malaria parasite to become dormant in the body which can at any time cause malaria relapses and resistance to malaria drugs.